Highly supportive hydrogen peroxide as a hole scavenger to improve the visible light water splitting activity of flake-like Co-doped ZnO thin films. (October 2019) - Sreedhar, Adem; Reddy, I. Neelakanta; Hoai Ta, Qui Thanh; Cho, Eunbin; Noh, Jin-Seo
Graphical abstract: Highlights: Enhanced PEC water splitting activity reported on flake-like Co-ZnO thin films. Hole scavenger activity of H2 O2 on Co (1.7 at.%)-ZnO improved the PEC activity. Cathodic currents greatly controlled by the addition of H2 O2 in KOH (7 × 10 −7 A/cm 2 ). Abstract: In the present work, we explored the hole scavenging activity of hydrogen peroxide (H2 O2 ) on flake-like Co-doped ZnO thin films to improve the visible light photoelectrochemical (PEC) water splitting activity. To address this phenomenon, we developed promising Co (0, 0.8, 1.7 and 2.2 at.%)-doped ZnO thin films by simultaneous RF and DC magnetron sputtering. First, precise control on Co doping level in the ZnO host lattice has been demonstrated to facilitate superior water splitting activity through the strategic surface transformation. Accordingly, Co doping concentration significantly modulated the structural properties of ZnO (0 0 2). From FESEM analysis, clear morphological changes were observed from granular (Co-0 at.%) to flake-like (Co-1.7 at.%). Also, AFM analysis provided insights into surface roughness (7.0 nm) and maximum height of roughness (35 nm) of Co (1.7 at.%)-ZnO thin films. Furthermore, TEM analysis highlighted the crystalline changes on Co (1.7 at.%)-ZnO thin films. Thus, Co (1.7 at.%)-ZnO exhibited a reduced band gap (3.07 eV). Notably, flake-like Co (1.7 at.%)-ZnO thin films validated with prominent hydrophilicity. As a result, the morphology of Co (1.7 at.%)-ZnO facilitated superior visible light PEC activity than others. Second, to accelerate the PEC activity, hole scavenging mechanism has been proposed by the addition of H2 O2 into the KOH. Our results show how the HO2 * radicals contributed to suppressing the hole accumulation, recombination and cathodic currents at the interface of Co-ZnO/electrolyte. Overall, we believe that the proposed hole scavenger strategy provides new insight into improved visible light PEC water splitting activity on flake-like Co-ZnO thin films.